Análise da imunoexpressão da isoforma alfa do receptor de glicocorticoide e de proteínas relacionadas à autofagia na carcinogênese labial - Sena, Luana Samara Balduino de (2021)
Chronic exposure to ultraviolet (UV) radiation is capable of causing cellular changes and culminating in the development of potentially malignant disorders, especially actinic cheilitis (AC). The rates of malignant transformation of this lesion into a squamous cell carcinoma (SCC) can reach 30%, but the molecular events involved in this process remain incompletely understood. Several studies have highlighted the participation of the glucocorticoid receptor isoform α (GRα) and autophagy, an important intracellular catabolic mechanism, in the development and progression of malignant neoplasms. Although GRα and autophagy are objects of intense scientific investigation, so far, little is known about their involvement in lip carcinogenesis. Thus, this study aimed to evaluate the immunoexpression of GRα and autophagy-related proteins (Atg7, LC3A, p62 and p-mTOR) in cases of AC and lower lip squamous cell carcinoma (LLSCC). The sample consisted of 40 cases of AC and 40 cases of LLSCC. Clinical data (patients’ sex and age, tumor size/extension, regional lymph node metastasis, distant metastasis and clinical stage) were collected in histopathological examination requisition forms and medical records. For the morphological study, the degree of epithelial dysplasia in the ACs and the histopathological degree of malignancy in the LLSCC invasion front were analyzed. In the immunohistochemical study, the percentages of positive epithelial cells (nucleus and cytoplasm) for GRα, Atg7, LC3A, p62 and p-mTOR were established in 5 microscopic fields of the epithelial lining of ACs and in 10 fields of the LLSCC invasion front. The data obtained were statistically analyzed using the Mann-Whitney and Spearman correlation tests (p < 0.05). GRα nuclear and cytoplasmic immunoexpression was found in all cases of AC and LLSCC, with high percentages of positivity. Compared to ACs, LLSCCs exhibited higher percentages of cytoplasmic expression (p < 0.001) and lower percentages of nuclear positivity for GRα (p = 0.021). On the other hand, ACs exhibited higher cytoplasmic expressions of LC3A (p < 0.001), p62 (p = 0.003) and p-mTOR (p < 0.001). Considering the clinicopathological parameters of the lesions, statistically significant differences were identified for the immunoexpression of GRα and LC3A. In this sense, LLSCCs with a high degree of malignancy had higher percentages of cytoplasmic positivity for GRα when compared to tumors with a low degree of malignancy (p = 0.016). Furthermore, in ACs, cases with a low degree of epithelial dysplasia exhibited higher percentages of nuclear positivity for LC3A when compared to cases with a high degree of epithelial dysplasia (p = 0.004). Both in ACs and LLSCCs, positive correlations were found between cytoplasmic and nuclear immunoexpression of all analyzed proteins (p < 0.05). Additionally, in LLSCCs and ACs, positive correlations were observed between the immunoexpression of autophagy-related proteins (p < 0.05). No significant correlations were found between the expressions of GRα and autophagy-related proteins in none of the groups (p > 0.05). In conclusion, the results of this study suggest that reduced nuclear translocation of GRα and upregulation of autophagy are important events in lip carcinogenesis, but are probably not involved in the progression of LLSCCs. In this process, the role of GRα may not be primarily related to the modulation of Atg7, LC3A, p62 and p-mTOR protein expressions.